(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the one who was sent as a mercy to the worlds, our master Muhammad Al-Amin, and his family and companions, and those who follow them in goodness until the Day of Judgment.To proceed: The study of Islamic jurisprudence from any aspect brings many benefits to the society in which we live, and to the entire world, and among these benefits: understanding the religion is one of the best deeds, as indicated by the Qur’anic texts and the honorable Sunnah of the Prophet. ِ ِ َ َ َ َ َ ْ َ َ َ ْ َ َ َ َ َ ََ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ ْ َ َ َ َْ َ َْ َْ َْ َْ َْ َْ َْ َْ َْ َْ ََْ ََْ ََْ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ ْ َ َ َ َ َ َ َ َ ْ َ َ ْ َ َ َ ْ َ َ ْ َ ِ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ To َ َ َ َ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ To